Asthma in adolescents, consequences of transition from pediatric to adult pulmonology - Zafirovski, Oliver; Dimitrievska, Deska; Zdraveska, Marija (Macedonian Respiratory Society, 2025)
Asthma is a complex, heterogenous medical condition which is very common in children and adults. Transition is “the purposeful, planned movement of adolescents and young adults with chronic physical and medical conditions from child-centered care to adult-oriented health care systems”. The significant changes in physical and mental health during this time, as well as the many unique developmental and psychosocial challenges that occur during adolescence can complicate and impede transition if not adequately addressed and managed. The transition period can also be a challenging time for health professionals to assess readiness for transition and manage some of the complications which are particularly common during this time, including poor adherence to therapy, smoking, drug use, and emerging mental health conditions. The natural history, presentation, symptoms, and management of asthma is often significantly different when comparing pediatric and adult practice. In addition, management in infants, toddlers, school aged children, and adolescents differs significantly, offering an additional challenge to pediatric physicians managing asthmatic children and young people. Despite these challenges, if the transition process for young people with asthma is planned and performed in a formalized manner, many of these issues can be addressed, allowing the transition to occur smoothly despite changes that may occur in medical and psychosocial domains. A successful transition, with minimal consequences, can only be achieved with the continuous cooperation of pediatric and adult pulmonologists.
Keywords: asthma; adolescent age; transition consequences